URGENSI PERLINDUNGAN HUKUM BAGI KORBAN KEKERASAN BERBASIS GENDER ONLINE DI INDONESIA - Sri Humana Lagustiani, (2021)
ABSTRACT This study aims, firstly to analyze the obstacles faced and the efforts made in providing legal protection to victims of online gender-based violence, secondly to analyze law enforcement against victims of online gender-based violence, especially in protecting the rights of victims. The type of research used is normative juridical law research which is prescriptive with legal, historical, conceptual and case approaches. The type of data used is secondary data. Legal protection for victims of online gender-based violence still does not have a clear regulation. The regulation of victims' rights is very important to be regulated in detail in the law. The Law on the Protection of Witnesses and Victims only regulates specifically for victims of certain crimes, namely victims of serious human rights violations, victims of criminal acts of terrorism, victims of criminal acts of trafficking in persons, victims of criminal acts of torture, victims of criminal acts of sexual violence, and victims of severe abuse. Therefore, it is necessary to revise the laws and regulations that have not regulated fairly on the legal protection of victims of online gender-based crimes so that there are no mistakes in their understanding and application. Efforts to prevent and overcome problems that arise from gender-based violence on social media/online require a penal and non-penal policy. The penal policy in overcoming gender-based violence is to reform the criminal law so that it can be expanded to fulfill legal protection for victims of online gender-based violence.